Comparative activity of CGP 31608, nafcillin, cefamandole, imipenem, and vancomycin against methicillin-susceptible and methicillin-resistant staphylococci. - Sachdeva, M (1987)
The activity of CGP 31608 for 53 strains of Staphylococcus aureus and 48 strains of S. epidermidis, both methicillin susceptible and resistant, was compared with that of vancomycin, nafcillin, cefamandole, and imipenem. Microdilution MICs were determined in Mueller-Hinton broth with or without 2.5% NaCl at an inoculum of 3 x 10(5) CFU/ml with a 20-h, 37 degrees C incubation. The MICs of imipenem and CGP 31608 for methicillin-resistant strains were lower than the MICs of nafcillin or cefamandole for these strains; these differences diminished in the presence of 2.5% NaCl. Subpopulations were detected in strains of methicillin-resistant S. aureus and S. epidermidis that were resistant to all the beta-lactam antibiotics tested at 5 micrograms/ml. This resistant subpopulation produced progeny that were uniformly resistant to high concentrations of each of the beta-lactams.